2021
DOI: 10.1002/bse.2742
|View full text |Cite
|
Sign up to set email alerts
|

Chief executive officers' sustainability orientation and firm environmental performance: Networking and resource contingencies

Abstract: Although the existing literature supports the relationship between chief executive officers' (CEOs') sustainability orientation (SO) and entrepreneurial behaviour, empirical studies exploring how SO drives firm environmental performance (FEP) are lacking. In addition, the potential moderating effects of firm-level factors on this relationship are less understood. We contribute to filling this gap by examining the moderating effects of political connections and financial slack on the relationship between SO and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 64 publications
(98 reference statements)
0
20
0
Order By: Relevance
“…In EO firms, the leaders can help develop or strengthen the integrity of the organizations. This finding is fascinating and relevant for the EO literature as it adds to the understanding of the link between EO and sustainable leadership behavior that influence firm performance, thus contributing to recent debates (Adomako et al, 2021;Wales et al, 2020). As regards the latter, it underlines, in particular, the need for leaders to have an in-depth understanding of the people and their characteristics.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In EO firms, the leaders can help develop or strengthen the integrity of the organizations. This finding is fascinating and relevant for the EO literature as it adds to the understanding of the link between EO and sustainable leadership behavior that influence firm performance, thus contributing to recent debates (Adomako et al, 2021;Wales et al, 2020). As regards the latter, it underlines, in particular, the need for leaders to have an in-depth understanding of the people and their characteristics.…”
Section: Discussionmentioning
confidence: 67%
“…EO is associated with innovativeness, risk-taking, and proactiveness (Covin & Slevin, 1989), and existing research suggests that leadership behavior influences the EO in organizations (Carraher, 2014;Engelen et al, 2015) by developing the organizational culture (Kunze et al, 2016) and allocating resources (Hambrick & Mason, 1984). While previous research has examined how leadership behavior influences entrepreneurial activity (e.g., Covin et al, 2020;Covin & Slevin, 1989;Engelen et al, 2015;Muchiri & McMurray, 2015;Wales et al, 2020), a critical gap remains in how employees' individual psychological characteristics influence sustainable leadership behavior in entrepreneurially oriented organizations (Adomako et al, 2021;Kraus, Burtscher et al, 2018), as suggested by Wales et al (2020), "…only a small number of studies examining the antecedents of EO" (p. 12). Additionally, research related to responsible and sustainable businesses are still emerging (e.g., Chavez et al, 2020;Marcus & Roy, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Eagly and Wood (1991) and Gilligan (1977Gilligan ( , 1982 describe that, based on their childhood experiences and social roles, women are more concerned with the welfare of others and have a more long-term orientation than men (see also Croson and Gneezy 2009;Fetchenhauer and Rohde 2002). Investments in sustainability are generally considered long-term (Porter and Miles 2013), and the attitude towards sustainability explains executives' CSR decision-making (Adomako et al 2021). As long-term orientation seems to be more prominent in women, the attitude towards sustainability might also be gender-dependent.…”
Section: Related Research and Hypotheses Developmentmentioning
confidence: 99%
“…In particular, we observe an interesting negative correlation between financial slack and environmental and social value orientation. There are extant studies advocating a positive relation (Adomako et al, 2021), which raises questions on the role of financial slack. Future endeavors may investigate how financial slack moderates the relationship between sustainability orientation and strategic resource allocations.…”
Section: Future Research Directions and Limitationsmentioning
confidence: 99%